Mediating role of emotion regulation strategies in the relationship of childhood traumas with risky alcohol-substance use and sexual compulsions - Kınay Demirezer, Şevval; Tamam, Lut (Journal of Dependence, 2025)
Objective: This study aims to investigate the mediating role of cognitive emotion regulation strategies in the relationship between childhood trauma, risky alcohol and substance use, and sexual compulsions.Method: The research involved 303 participants from universities in Ankara. Data collection included the Childhood Trauma Questionnaire, Sexual Compulsions Scale, Addiction Profile Index Risk Screening Scale, and Cognitive Emotion Regulation Questionnaire. The relationships between the variables were analyzed using correlation, simple linear regression, and Model 4 for mediation analysis.Results: The study found that childhood trauma significantly predicted risky alcohol and substance use, sexual compulsions, and maladaptive cognitive emotion regulation strategies. Additionally, maladaptive emotion regulation strategies were found to significantly impact sexual compulsions. The analysis also revealed that childhood trauma influences sexual compulsions through these maladaptive strategies, highlighting the crucial role of cognitive emotion regulation in the development of addictive behaviors.Conclusion: Childhood trauma and cognitive emotion regulation strategies are vital factors in addiction risk processes. These results suggest that interventions targeting emotion regulation could help address maladaptive behaviors linked to trauma and addiction, providing valuable insights for researchers and practitioners.
Keywords: Sexual compulsion; childhood trauma; emotion regulation; risky alcohol use